Edukasi Keluarga Pengasuhan 1000 HPK untuk Pencengahan Stunting di Desa Cibatok 2 - Dwi Kurniati Putri; Tin Herawati; Alfiasari Alfiasari; Yulina Eva Riany; Melly Latifah; Dwi Hastuti; Irni Rahmayani Johan; Mohammad Nur Indro (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Education about the care of the first 1000 days of birth (1000 HPK) is important to familes, as the main capital in the delovpment of a prosperous family and the formation of quality resources. Nurture is a long process in the life of child and it starts form the prenatal period until the adulthood. This service activity aims to increase aims to increase target participation to be involved in family education, increase maternal knowledge related to affirmation of family functions and nurture for the first 1000 days of birth, and mothers have skliss related to growing hydroponic vegetables. Methods of family education activities are counseling and QnA. Family education activities has been implemented 7 times with 90 minutes per one meeting. Before the counseling, the target audience (mother who has a two-year-old baby) was given information concent and pre-test activities questionnaire. After being counseled, a post test was conducted with the same questions. The result of this activity showed considerable enthusiasm and community participation, increased maternal knowledge anout nurture of the first 1000 days of birth, and new skills related to houssehold waste utilization for hydroponic planting. The relevant stakeholders such as the family planning field officers (PLKB) Cadre and Posyandu Cadre are expected to cunduct routinely family education in Posyandu monthly activities, it also can increase the community productivity and economy with planting and farming.